An analysis of the laws governing cyber terrorism in Malaysia / Fateha Mohd Amir Saripudin...[et al.] - Mohd Amir Saripudin, Fateha; Razali, Ayudiana; Wan Chik, Wan Nur Munirah (2011)
This project focuses on the laws governing cyber terrorism in Malaysia. Currently, cyber terrorism is governed by the Penal Code and the Internal Security Act 1960. There are three main objectives of this project. Firstly, the project aims to critically analyze the sufficiency of the laws that governing cyber terrorism is. Secondly, the project critically examines the laws on cyber terrorism in the United Kingdom (UK), the United States (US), and Australia for the purpose of making a legal comparison of the study. Thirdly, the project proposes some recommendations for the improvement of the current laws governing cyber terrorism in Malaysia. The project highlights the legal issues in the current legislation and the critiques of such laws. Also, the project engages in the theoretical level of the study, showcasing the relevance of the theory of risk, particularly, the theory of economic risk to the crime of cyber terrorism. Based on the comparative analysis, this project found that there is a need for Malaysia to have a specific law in governing the offence of cyber terrorism. As conclusion, this research provides several recommendations for the improvement of the current laws on cyber terrorism in Malaysia.